I am potential - Jenkins, Burgess, 1973-; Bellinger, Jimmy; Reinhold, Judge, 1957-; Williamson, Jama; Meiners, Zach; American Family Studios (United States American Family Studios, 2015)
Patrick Henry Hughes was a talent musician who always wanted to be a part of something bigger than himself. He dreamed of one day joining the University of Louisville marching band but there was one problem: Patrick Henry was born without eyes or the ability to walk. Before he was even born, his father Patrick John had his own goals for Patrick Henry. Now, he must sacrifice all that to help his son achieve his dream. This is the inspiring true story of sacrifice, perseverance, and realizing one's potential."--Container
Widescreen (2.35:1).
Special features include: Creating Potential: Becoming the Hughes family; Magnetic dreams on visual effects; B.J Davis on music composition.
Original score by BJ Davis.
Burgess Jenkins, Jimmy Bellinger, Jama Williamson with Judge Reinhold.
DVD.
English; closed-captioned; English subtitled for the deaf and hard of hearing.
Keywords: Musicians with disabilities; Blind musicians; Video recordings for the hearing impaired; Fiction films; Feature films; Drama